Microwave-resonance-induced magnetooscillations and vanishing resistance states in multisubband two-dimensional electron systems - Monarkha, Yu.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The dc magnetoconductivity of the multisubband two-dimensional electron system formed on the liquid heliumsurface in the presence of resonant microwave irradiation is described, and a new mechanism of the negative linear response conductivity is studied using the self-consistent Born approximation. Two kinds of scatterers (vapor atoms and capillary wave quanta) are considered. Besides a conductivity modulation expected near the points, where the excitation frequency for inter-subband transitions is commensurate with the cyclotron frequency, a sign-changing correction to the linear conductivity is shown to appear for usual quasi-elastic inter-subbandscattering, if the collision broadening of Landau levels is much smaller than thermal energy. The decay heatingof the electron system near the commensurability points leads to magnetooscillations of electron temperature, which are shown to increase the importance of the sign-changing correction. The line-shape of magnetoconductivity oscillations calculated for wide ranges of temperature and magnetic field is in a good accordance with experimentalobservations.